2020
DOI: 10.1017/s1041610220000344
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural dementia screening using the Rowland Universal Dementia Assessment Scale: a systematic review and meta-analysis

Abstract: Objectives: To quantitatively synthesize data on the accuracy of the Rowland Universal Dementia Assessment Scale (RUDAS) in different sociocultural settings and compare its performance to other brief screening instruments for the detection of dementia. Design: Systematic review and meta-analysis. Literature searches were performed in PubMed, EMBASE, and CINAHL from January 1, 2004 until September 1, 2019. Setting: Community, outpatient clinic, and hospital settings in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…The original RUDAS study with a cut-off of 23 had sensitivity and specificity of 89% and 98% [11,12]. A systematic review and meta-analysis [20] showed that the performance of RUDAS varied with cut-off values and between studies. As evaluated from the Youden index, our data suggest a cut-off at ≤23 for detecting cognitive impairment, supported by best-combined sensitivity and specificity at 100% and 75.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The original RUDAS study with a cut-off of 23 had sensitivity and specificity of 89% and 98% [11,12]. A systematic review and meta-analysis [20] showed that the performance of RUDAS varied with cut-off values and between studies. As evaluated from the Youden index, our data suggest a cut-off at ≤23 for detecting cognitive impairment, supported by best-combined sensitivity and specificity at 100% and 75.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used screening instrument is not always adjusted for use when assessing patients born in other countries (Ardila, 2005;Daker-White et al, 2002;Naqvi et al, 2015;Nielsen et al, 2015;Nielsen, Vogel, Phung, et al, 2011a;Plejert et al, 2015;Sagbakken et al, 2018). RUDAS, The Rowland Universal Dementia Assessment Scale, is a cognitive screening instrument that is less affected by the patient's linguistic, cultural and educational background (Nielsen & Jorgensen, 2020;Nielsen et al 2017). This test is currently used in several countries including Sweden.…”
Section: Dementia Assessment Of Non-native Swedish Patientsmentioning
confidence: 99%
“…RUDAS [21], developed in Australia, is an efficient test with strong dementia psychometric properties, which was specifically developed for use with people from diverse linguistic and cultural backgrounds [22]. The test is considered to have good accu-83 racy for detecting dementia in various socioeconomic 84 and educational settings, even for those without any 85 formal education [16,22]. The test can be used in dif-86 ferent languages without any adjustment or changes 87 in the test [16,21].…”
Section: Possibilitiesmentioning
confidence: 99%